Uji Klinik Terdesentralisasi: Mendefinisikan Ulang Partisipasi, Kuasa, dan Presisi dalam Riset Kesehatan - Raymond R. Tjandrawinata (PT Dexa Medica, 2025)
Decentralized clinical trials (DCTs) have emerged as a transformative force in biomedical research, breaking down traditional boundaries and reshaping how evidence is generated, validated, and applied. By leveraging digital health technologies, real-world data, and remote engagement infrastructures, DCTs have the potential to democratize clinical research by improving inclusivity and accessibility. However, these opportunities come with challenges related to regulatory governance, technological ethics, and socio-political representation. This brief article explores both the conceptual and empirical foundations of DCTs, drawing from recent studies, international policy documents (such as white papers), regulatory initiatives, and global practice surveys. It examines the epistemological, operational, and normative shifts introduced by DCTs and proposes a framework for understanding their impact on three core dimensions of clinical science: participation, power, and precision. Ultimately, this article argues that DCTs are not merely a digital enhancement, but rather a fundamental reconfiguration of how health knowledge is generated and governed.